THE ROLE OF TELEDENTISTRY IN ENHANCING DIAGNOSIS, CONSULTATION, AND POST-OPERATIVE CARE IN RESTORATIVE DENTISTRY: A REVIEW ARTICLE - Rayan A. Hawsawi (Romanian Journal of Oral Rehabilitation)
Within the current digital advancement of the dental field in all aspects, teledentistry has become one of the essential tools that enables fast and accurate diagnosis, and thus high-quality treatment and improved outcomes. This review explores the role of teledentistry in improving diagnosis, consultation and post operative management of the different dental restorative specialties. It was conducted using PubMed, Scopus, and Google Scholar databases. Recent estimates indicate that over 63% of the global population actively uses the internet. It was found that teledentistry gives the advantage to the underserved rural areas to access advanced consultation and diagnosis from specialized health care providers. Consultations and teledentistry assessments were found to achieve comparable diagnostic accuracy rates to in-person evaluations of up to 85%. The findings showed that the use of teledentistry reduces patient waiting times, referral rates, and in-office waiting times, while maintain a high patient satisfaction. Additionally, it offers access to expert opinions within specialized fields and proves invaluable for remote patient management and monitoring, although some challenges associated with teledentistry stem from technical issues. In conclusion, teledentistry significantly enhances overall diagnosis, management, outcomes, and the patient experience. However, further improvements are still needed.